LED Goniometry System - Svilainis, L.; Dumbrava, V. (Elektronika ir Elektrotechnika, 2006)
The light emitting diode (LED) directional parameters measurement system is analysed. It has been indictaed that postioning uncertainty is the major contributing member in LED peak emission angle Θpeak measurement. The LED half power emission angle Θ0.5 combined uncertainty is mainuly contributed by radiometry sensor nonlinearity. New measurement system has been developed basing the prototype system. The new computer – controlled system design aproach is described. System capabilities are demostrated by farfield- pattern (FFP) measurement results of various manufacturers LEDs. The meaured LED FFP are recalculated into totaling whole screen directivity diagramms using the averaged LED FFP from multiple measurements. The diagramms are presented both in Cartesian and polar koordinate system. Ill.14, bibl.10 (in English; summaries in English, Russian and Lithuanian).